THE STORY OF CANCER: DOWN THE RABBIT-HOLE: The Story of Cancer: Down the Rabbit-Hole - Hasan, Nadir (Pakistan Armed Forces Medical Journal, 2014)
From the earliest of times, human beings have lived in awe of the forces of Nature, and agonised over the (often) cruel edicts of Destiny and Fate. In the Quatrain quoted above, the great Muslim poet and mathematician Omar Khayyam, most eloquently, refers to this very conundrum. Why is there so much sorrow, pain, and (from a bio-medical perspective) disease, in this World of ours?